Gamification in Young EFL Learning: A Thematic Review of Motivation, Engagement, and Language Outcomes - Tajrian Rahman Mou (Journal of Applied Linguistics, 2026)
The implementation of gamification in English as a Foreign Language education for young learners has attracted increasing interest because it provides methods to boost student motivation and classroom participation while enhancing their language skills. Current research shows incomplete evidence because studies have been conducted in different settings and researchers have studied different results. The research study intends to present a thorough analysis of how gamification affects the motivation and engagement and vocabulary development and speaking abilities of young EFL students. The research conducted through a qualitative thematic review by analyzing 42 peer-reviewed studies which were published between 2019 and 2025. This research collected data from major academic databases and used Braun and Clarke's (2006) thematic analysis framework to conduct their analysis. The research results show that gamification implementation leads to higher levels of motivation because it decreases language anxiety while increasing both behavioral and emotional engagement of students. The program provides students with measurable improvements in their vocabulary and spoken language development. The success of gamification implementation depends on three main factors which include the learner characteristics and the learning environment and the specific game design elements. The research study demonstrates that EFL classrooms can benefit from gamification as an effective teaching method when educators design their implementation to meet student requirements and follow specific instructional guidelines and adapt to their existing classroom environment. Keywords : Gamification; young learners; EFL; motivation; student engagement; speaking skills